Life table, infestation and interaction of papaya mealbug Paracoccus marginatus Williams & Granara de Willink (Pseudococcidae: Hemiptera) and its parasitoids - Mastoi, Muhammad Ishaque (2014)
The papaya mealybug, Paracoccus marginatus Williams and Granara de Willink (Hemiptera: Pseudococcidae) is a serious pest of papaya. This exotic pest cause a serious problem if, indigenous natural enemies are not available. This pest was never studied in Malaysia although severe infestation of this unidentified mealybug was reported by papaya farmers. This study therefore, was initiated to investigate the life table of papaya mealybug, Paracoccus marginatus (Hemiptera: Pseudococcidae), its infestation and interaction with natural enemies. Life table study of P. marginatus was initiated on four cohorts, each consisting of 137, 120, 102 and 100 eggs. Agespecific survival life table indicated that 64.27% P. marginatus eggs successfully reached to adults with a sex ratio of 1.09:1 (Female: Male). The pattern of survivorship curves (lx) falls in type III indicating highest mortality in offsprings. The highest mortality was recorded in first instar nymphs (20.09%) with k-value of 0.097. Age-specific fecundity (mx) of P. marginatus showed earliest egg laying on day 25 and continued till death of female. The last female died on day 47. The female laid on average 275.91±8.10 eggs. The maximum (74.90%) eggs laid were during 27th to 33rd day. The intrinsic rate of natural increase (rm) of P. marginatus was 0.12 per female per day and the daily finite rate of increase (λ) was 1.13 female offsprings per female per day with mean generation time (Tc) of 30.72 days. The net reproductive rate (R0) was 43.36 female offsprings per female. Doubling time was recorded as only 5.65 days. Survey for infestation of P. marginatus was done in two states, namely Negeri Sembilan and Selangor, to confirm the pest status in Peninsular Malaysia. A total of ten locations were surveyed for the infestation. All aerial plant parts of the papaya plants including leaves, fruits and stem were observed because pest attacks only aerial plant parts except roots. Results indicate that the pest infestation was observed in both states. This pest was also found infesting seven other host plants (Hibiscus, Cassava, Plumeria, Roselle, Eggplant, Jatropha and Broad beans). During observation, two predators, Apertochrysa sp. and Cryptolaemus montrouzieri and, one primary parasitoid, Acerophagus papayae and three secondary parasitoids viz. Chartocerus sp., Marietta leopardina and Cheiloneurus sp. were found on P. marginatus. Out of 7965 mummies of P. marginatus collected, A. papayae showed higher (95.22%) population frequency. However, secondary parasitoids remained lower than 5%. The study on weekly population fluctuation of P. marginatus and its natural enemies on papaya in five locations within vicinity of Universiti Putra Malaysia showed the highest mean P. marginatus population (7.02 per 25 cm2 leaf area) in Sri Serdang. The maximum population of P. marginatus was found on the basal part of papaya leaf compared to middle and apical leaf parts. The population of Apertochrysa sp. on papaya was comparatively higher (0.48 per 25 cm2 leaf area) in Ladang-2. The population of C. montrouzieri ranged between 0.33 to 0.54 per 25 cm2 leaf area. The A. papayae population was higher (1.36 to 2.00 per 25 cm2 leaf area) at Faculty of Agriculture (old), Ladang-2, Bukit Expo and Sri Serdang. The population of P. marginatus remained higher in the month of August, thereafter, declined due to appearance of natural enemies. Similarly, the population of predators (Apertochrysa sp. and C. montrouzieri) and parasitoid (A. papayae) was high during August and declining in the following months. Among the weather parameters, only temperature showed significant effect on the population fluctuation of P. marginatus, whereas significant effect of two predators, C. montrouzieri and Apertochrysa sp. and a parasitoid, A. papayae was observed on the P. marginatus population. Studies on A. papayae was conducted on different host stages of P. marginatus viz. second instar male, second instar female, third instar female and adult female in choice and no-choice situations. All the treatments were replicated ten times. The highest percent parasitism was recorded in second instar female (59±5.66%) in no choice situation. However, in choice situation no specific trend of parasitism was found. In choice and no choice situations, the male-biased sex ratio was observed in second instar male P. marginatus and the female-biased sex ratios in all female stages of P. marginatus with longer developmental time in females. Interestingly, A. papayae showed gregarious behavior in adult female P. marginatus while solitary in rest of instars in both choice and no choice experiments.